2020
DOI: 10.1016/j.childyouth.2020.104961
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes of mental illness stigma in children and adolescents: A mixed-methods systematic review

Abstract: Background: Mental illness stigma has serious psychological and social consequences for adults, and remains a significant barrier to help-seeking. The aim of this review was to synthesise findings from qualitative and quantitative studies investigating the psychosocial effects of mental illness stigma in youth with mental health problems who access services.Methods: Four databases were searched resulting in 3,353 abstracts with 27 studies included for synthesis. Participants ranged from 8-19 years old across s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…When examining specific mental health diagnoses, we noted that a majority of individual mental disorder diagnoses were associated with experiencing barriers to accessing services (including, but not limited to, anxiety, depression, anorexia or bulimia, and OCD; full results can be seen in Table 2 ). This finding supports a strong body of research suggesting that different mental illnesses are associated with varying levels of stigma, social acceptability, and treatment options [ 33 ]. Moreover, youth belonging to gender and sexual minority groups face unique experiences of mental health that intersect with their gender and sexual identities [ 1 , 5 , 10 ].…”
Section: Discussionsupporting
confidence: 83%
“…When examining specific mental health diagnoses, we noted that a majority of individual mental disorder diagnoses were associated with experiencing barriers to accessing services (including, but not limited to, anxiety, depression, anorexia or bulimia, and OCD; full results can be seen in Table 2 ). This finding supports a strong body of research suggesting that different mental illnesses are associated with varying levels of stigma, social acceptability, and treatment options [ 33 ]. Moreover, youth belonging to gender and sexual minority groups face unique experiences of mental health that intersect with their gender and sexual identities [ 1 , 5 , 10 ].…”
Section: Discussionsupporting
confidence: 83%
“…14 An effective strategy, such as strong interventions from the central/regional government, religious leaders, and security forces, is necessary to eliminate the negative stigma associated with COVID-19, reduce community anxiety, improve the status of victims, andoptimize the resources ofthe community. 15 Therefore, the patient's families and the health workers who survive should not be isolated from the community because of stigma. Even if one does not want to help these individuals, patients and their families should not experience additional stress associated with stigma, judgments, and even insults.…”
Section: Discussionmentioning
confidence: 99%
“…These 3 studies (Moses 2009a(Moses , 2009b(Moses , 2010 which discussed self-stigma shared a sample of 60 young people. Ferrie et al, (2020) note that 10 of the 27 papers included in their review discuss self-stigma. This suggests that there is a lack of research exploring mental illness self-stigma in young people.…”
mentioning
confidence: 99%
“…A preliminary search for existing scoping reviews and systematics reviews has been conducted; APA PsycInfo, Web of Science and MEDLINE were searched on 02/07/2021. As a result, 4 reviews were found; 2 systematic reviews which focused generally on stigma in young people (Kaushik et al, 2016;Ferrie et al, 2020), a systematic review protocol exploring stigma in Middle Eastern adolescents (Mohammadzeh et al, 2020) and a systematic review on the mediating effect of self-stigma and depressive symptoms on self-harm and bullying victimisation (Karanikola et al, 2018). However, no scoping reviews or systematic reviews specifically focusing on mental illness self-stigma in young people are known to exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation